Solve the following system:
{x = y + 1 | (equation 1)
{4 x - 5 y = -9 | (equation 2)
Express the system in standard form:
{x - y = 1 | (equation 1)
{4 x - 5 y = -9 | (equation 2)
Swap equation 1 with equation 2:
{4 x - 5 y = -9 | (equation 1)
{x - y = 1 | (equation 2)
Subtract 1/4 × (equation 1) from equation 2:
{4 x - 5 y = -9 | (equation 1)
{0 x+y/4 = 13/4 | (equation 2)
Multiply equation 2 by 4:
{4 x - 5 y = -9 | (equation 1)
{0 x+y = 13 | (equation 2)
Add 5 × (equation 2) to equation 1:
{4 x+0 y = 56 | (equation 1)
{0 x+y = 13 | (equation 2)
Divide equation 1 by 4:
{x+0 y = 14 | (equation 1)
{0 x+y = 13 | (equation 2)
Collect results:
Answer: {x = 14
{y = 13